Islamic Ethical Values as The Foundation for The Use of Artificial Intelligence in Islamic Boarding School Education - Mujahid, Abdul Rahman; Mustofa, Triono Ali; Jinan, Mutoharul (Universitas Muhammadiyah Surakarta, 2025)
The growing use of Artificial Intelligence in education presents both opportunities and ethical challenges for Islamic boarding school (pesantren) education. While Artificial Intelligence may enhance learning efficiency and institutional management, its integration within pesantren must be guided by ethical principles rooted in Islamic values. This article examines the use of Artificial Intelligence in pesantren education through the framework of Islamic ethics, emphasizing trust (amanah), justice (‘adl), responsibility (mas’uliyyah), and ethical conduct (adab) as foundational principles. Using a qualitative conceptual approach, the study analyzes Islamic ethical perspectives as a normative foundation for evaluating and guiding the adoption of Artificial Intelligence in pesantren education. The findings indicate that Artificial Intelligence should not be treated as a neutral or autonomous technology, but as a moral instrument that remains under human authority and ethical accountability. The article also identifies key ethical challenges, including algorithmic bias, the erosion of human responsibility, data privacy concerns, and the tendency toward instrumental approaches to education. Furthermore, the study highlights the pedagogical, institutional, and moral implications of Artificial Intelligence use in pesantren education, particularly in preserving educators’ roles, ensuring ethical governance, and supporting students’ moral and character development. The article concludes that a human-centered and value-oriented approach is essential to ensure that Artificial Intelligence contributes positively to pesantren education without compromising its moral and spiritual mission.